TECHNOLOGY ACCEPTANCE MODEL ON DIGITAL BANKING SERVICE LIVIN' BANK MANDIRI ON TRUST AND ITS IMPACT ON CUSTOMER LOYALTY - Ria Marlina; Jerry Heikal (Jurnal Scientia, 2023)
This study aims to test the expected research model and be able to obtain the results of the influence of the technology acceptance model on digital banking services livin' Bank Mandiri on trust and its impact on customer loyalty. Questionnaire respondent data was obtained from Bank Mandiri customers who had used digital banking service livin' Bank Mandiri' and then distributed questionnaires online through the "Qualtric" platform to 150 respondents. In this study, 5 hypotheses were tested based on variable indicators that had been compiled using SEM PLS (partial least squares) analysis with the SmartPLS method. The test consists of the Outer Model, namely: Convergent Validity Test, Discriminant Validity Test, Average Variance Extracted (AVE) Test, Composite Reliability Test, Cronbach Alpha Test. Then testing the inner model, namely the results of Bootstrapping. Testing the hypothesis which shows that there is a relationship that has a direct positive and significant effect includes: H1: Perceived Usefulness on Customer Loyalty, H2: Perceived Ease of Use on Customer Loyalty, H3: Perceived Usefulness on Customer Trust. H4: Perceived Ease of Use on Customer Trust, H5: Customer Trust on Customer Loyalty. This research is expected to provide good implications theoretically and for further research. In addition, the implications of this research are also expected to provide input to other banking companies to create better customer loyalty.